A Floating Sheet for Efficient Photocatalytic Water Splitting. Issue 15 (31st May 2016) - Lin, Zhaoyong; Li, Jiling; Zheng, Zhaoqiang; Li, Lihua; Yu, Lili; Wang, Chengxin; Yang, Guowei
Abstract : Solar photocatalytic water splitting has been a promising way to provide clean hydrogen energy. There are two weaknesses in the typical photocatalytic process in which photocatalysts are generally dispersing in water under stir. One is the inadequate utilization of light energy and the other one is the cumbersome operation in the recycling procedure. This study demonstrates an efficient solar photocatalytic water splitting using a floating sheet with a novel WSe2 cocatalyst. The sheet is fabricated by laser‐depositing WSe2 film on a carbon foam (CF) substrate and drop‐casting of the synthesized nanodiamond‐embedded Cu2 O (NEC) photocatalysts. This is a new‐type artificial photocatalytic system that overcomes the above‐mentioned weaknesses of a powder‐dispersing system. The WSe2 cocatalyst acts as an electron sink to promote electron–hole separation, resulting in the further improvement of photocatalytic performance. This floating NEC/WSe2 /CF structure achieves efficient water splitting upon simulated solar irradiation with an increased H2 evolution rate, which is 13.2 times that of the powder‐dispersing system. This study offers a strategy for the design of new‐type photocatalytic system and discovery of alternative noble metal‐free cocatalysts. Abstract : A floating sheet for efficient solar photocatalytic water splitting is demonstrated. This new type of artificial photocatalytic system employs an excellent photocatalyst of nanodiamond‐embedded Cu2 O nanocrystal and a novel cocatalyst of WSe2 film on a carbon‐foam sheet. An improved H2 evolution activity is achieved, which is 13.2 times that of a typical powder‐dispersed system.